Hubungan Pengetahuan dan Reflkesi Tentang Kode Etik Kedokteran (KODEKI) dengan Sikap Dokter Muda dalam Berkomunikasi dengan Pasien - Aprilya Nur Widiastuty; Tissa Octavira P; Ouve Rahadiani P (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Communication between doctors and patients is a crucial component of health services, as it facilitates shared decision-making, improves diagnostic accuracy, and reduces patients’ anxiety regarding their illness. Data from the Indonesian Medical Disciplinary Board (MKDKI) in March 2011 reported 127 cases of professional misconduct, with approximately 80% caused by poor doctor-patient communication. This study aims to examine the relationship between knowledge and reflection of the Indonesian Medical Code of Ethics with young doctors’ communication attitudes. This observational study employed primary data collection with a stratified random sampling method involving 183 respondents from the Medical Profession Program, Faculty of Medicine, Universitas Swadaya Gunung Jati. Data were analyzed using Spearman’s test. The findings revealed a significant relationship between knowledge of medical ethics and communication attitudes (p=0.000) with a strong positive correlation among first-year (r=0.756) and second-year (r=0.649) young doctors. Reflection on medical ethics also showed a significant relationship (p=0.000) with a moderately strong positive correlation among first-year (r=0.693) and second-year (r=0.643) young doctors. In conclusion, both knowledge and reflection on the medical code of ethics are significantly associated with young doctors’ communication attitudes when interacting with patients